2016
DOI: 10.1038/nmeth.3863
|View full text |Cite
|
Sign up to set email alerts
|

Automated mapping of phenotype space with single-cell data

Abstract: Accurate and rapid identification of cell populations is key to discovering novelty in multidimensional single cell experiments. We present a population finding algorithm X-shift that can process large datasets using fast KNN estimation of cell event density and automatically arranges populations by a marker-based classification system. X-shift analysis of mouse bone marrow data resolved the majority of known and several previously undescribed cell populations. Interestingly, previously known cell populations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
455
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 381 publications
(460 citation statements)
references
References 25 publications
5
455
0
Order By: Relevance
“…Single-cell suspensions of hindlimb muscles, Gastrocnemius (GA) and Tibialis Anterior (TA) were prepared from 8-week old mice as described previously 10 and processed for CyTOF analysis (Fig.1b). To distinguish stem and progenitor cell populations, we analyzed the CyTOF dataset with a recently developed K-nearest neighbor density-based clustering algorithm called X-shift 13 , which performed unsupervised clustering analysis of cells within the myogenic compartment, defined as Lineage − /α 7 integrin + cells and subsequently refined to Lineage − /α 7 integrin + /CD9 + cells. With this new multivariate algorithm six clusters were generated, based on the expression of known and previously unrecognized surface markers, and key myogenic transcription factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-cell suspensions of hindlimb muscles, Gastrocnemius (GA) and Tibialis Anterior (TA) were prepared from 8-week old mice as described previously 10 and processed for CyTOF analysis (Fig.1b). To distinguish stem and progenitor cell populations, we analyzed the CyTOF dataset with a recently developed K-nearest neighbor density-based clustering algorithm called X-shift 13 , which performed unsupervised clustering analysis of cells within the myogenic compartment, defined as Lineage − /α 7 integrin + cells and subsequently refined to Lineage − /α 7 integrin + /CD9 + cells. With this new multivariate algorithm six clusters were generated, based on the expression of known and previously unrecognized surface markers, and key myogenic transcription factors.…”
Section: Resultsmentioning
confidence: 99%
“…With this new multivariate algorithm six clusters were generated, based on the expression of known and previously unrecognized surface markers, and key myogenic transcription factors. In order to visualize the spatial relationships between the cell types within these X-shift clusters, 2000 randomly sampled cells from each cluster were subjected to a force-directed layout 1315 . The resultant map revealed that cells fell densely into three prominent clusters and were linked by sparsely populated paths (Fig.1c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2c). We found that Mahalanobis distance was superior to other distance metrics (cosine 14,16 , Euclidian 17 , and Manhattan 18 ) in assigning cells to the correct developmental population (Supplementary Fig. 2d).…”
Section: Resultsmentioning
confidence: 91%
“…Three experts independently gated the cellular populations in the PANORAMA dataset and only the consensus part of the gating was retained. All event measurements were transformed by sinh-1((x-1)/5) before further processing (Samusik et al , 2016). …”
Section: Methodsmentioning
confidence: 99%